Implementasi media Wordwall dalam pembelajaran akidah akhlak di MA Al Hikam Jatirejo - Nur Lailatul Fitri; Ali Said (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to analyze the implementation of wordwall media in faith and morals learning at MA Al-Hikam Jatirejo Diwek Jombnag and its ability to improve the effectiveness of the learning process, especially in the subject of faith and morals. The use of wordwall media shows that teachers have utilized media as a are more interesting for students. This study uses a qualitative case study method with data collection techniques through observation, interviews, documentation, and triangulation. The result of the study indicate that wordwall media is able to increase students engagement and motivation because the presentation of material and evaluation is more varield and interactive. Faith and morals learning takes place through the stages of planning, implementation, and closing that refer to the independent curricuclum teaching module. The implementation of wordwall media has been proven to clarify the material, reducce bboredom, and strengthen student understanding. These findings confirm that the integration of wordwall media in faith and morals learning has a positive impact on students activity, understanding, and learning experiences, andis an effective and relevant alternative learning medium.